The standard aqueous stem bark extract of Mangifera indica L. inhibits toxic PLA2 - NN-XIb-PLA2 of Indian cobra venom - Bhadrapura Lakkappa Dhananjaya; Shivalingaiah Sudarshan; Yashad Dongol; Sunil S. More (Elsevier, 2016)
The aqueous extract of Mangifera indica is known to possess diverse medicinal properties, which also includes anti-snake venom activities. However, its inhibitory potency and mechanism of action on multi-toxic snake venom phospholipases A2s are still unknown. Therefore, the objective of this study was to evaluate the modulatory effect of standard aqueous bark extract of M. indica on NN-XIb-PLA2 of Indian cobra venom. The in vitro sPLA2, in situ hemolytic and in vivo edema inhibition effect were carried out as described. Also the effect of substrate and calcium concentration was carried out. M. indica extract dose dependently inhibited the GIA sPLA2 (NN-XIb-PLA2) activity with an IC50 value of 7.6 μg/ml. M. indica extract effectively inhibited the indirect hemolytic activity up to 98% at ∼40 μg/ml concentration. Further, M. indica extract (0-50 μg/ml) inhibited the edema formed in a dose dependent manner. When examined as a function of increased substrate and calcium concentration, there was no relieve of inhibitory effect of M. indica extract on the NN-XIb-PLA2. Further, the inhibition was irreversible as evident from binding studies. The in vitro inhibition is well correlated with in situ and in vivo edema inhibiting activities of M. indica. As the inhibition is independent of substrate and calcium and was irreversible, it can be concluded that M. indica extract mode of inhibition could be due to direct interaction of components present in the extract with the PLA2 enzyme. The aqueous extract of M. indica effectively inhibits svPLA2 enzymatic and its associated toxic activities, which substantiate their anti-snake venom properties. Further in-depth studies on the role and mechanism of the principal constituents present in the extract, responsible for the anti-PLA2 activity will be interesting to develop them into potent antisnake component and also as an anti-inflammatory agent.